Pre-operative chemoradiation for a patient with locally advanced cancer of the rectum complicated by a left pelvic kidney: A case report from cancer diseases hospital, Lusaka – Zambia (Indian Journal of Case Reports, 2020)
Neoadjuvant chemoradiotherapy (CRT) for rectal cancer complicated by a left pelvic kidney is presented as a case report here. A 38-year-old lady was seen with locally advanced rectal cancer. The computed tomography scan also showed an ectopic left pelvic kidney. The patient was planned for radical CRT and was to receive 45 Gy to pelvis plus a 5.4 Gy as a rectal boost. The concurrent chemotherapy was 5-fluorouracil and leucovorin. This was with 2D treatment planning technic which poses a big risk for permanent kidney damage. The 2D treatment plan, however, appeared to be sufficient even though the mean tolerance doses of 15–18 Gy for the kidney could not be proved. This, however, could be at the expense of tumor control.